The Implementation of Islamic Banking System in Malaysia: Awareness among Banking Staff (Global Business Management Review (GBMR), 2022)
In Malaysia, a relatively new but fast developing sub-sect of the financial sector is the Islamic banking and industry. Despite its recent history, Malaysia’s Islamic Banking institutions (IBIs) have dramatically increased in number and currently have seventeen (17) full-fledged and emerging Islamic Banking Institutions. It has been observed that despite the current global economic recession, the Islamic finance and banking industry has sustained its growth at extraordinary levels, having now become an essential part of global financial services landscape. The development of IBIs normally has been effected by internal and external environment, but the most important of development is on IBIs’ products and services. The aim of this paper is provide a conceptual understanding on history and development of IBIs by exploring the awareness facing by banking staff towards Islamic banking systems in Malaysia.